Implementation Of Google Classroom Application In Islamic Religious Education Learning At SMK Raden Rahmat Mojosari Mojokerto - Maghfiroh, Asmaul; Yusuf, Achmad (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2022)
This researched aims to : 1) learning plans of Islamic education to use google classroom in vocational Raden Rahmat, 2) learning Islamic education by using google classroom in vocational Raden Rahmat, 3) evaluation of learning Islamic Education by using google classroom at SMK Raden Rahmat. Based on research that has been conducted, the results showed by choosing google classroom as a learning medium. The First Planning for google classroom at SMK this Raden Rahmat doing a joint meeting during the 19th COVID beginning of each semester through zoom and offline applications, setting up RPP PAI, Develop the PAI syllabus, prepare learning media in accordance with the respective fields of the teacher, There is a circular from Nadiem Makarim. Second2. Proses Islamic religious education learning to use google classroom in vocational Raden Rahmat is to prepare the course material in advance, before use google classroom but before I directed learning in advance using watshapp that it will immediately begin learning, students study the learning material given by the teacher then do their work, educators sometimes give a deadline of one week or three days to submit the assignment to google classroom or e-mail. 3. Evaluation of Islamic Religious Education learning by using google classroom at Raden Rahmat Vocational School is carried out once a week with material being given, the following week given assignments, from that task we can assess the activity of children in participating in online learning. Keywords: Implementation, Google Classroom, Islamic Religious Education Learning.